Desempenho e rendimento da carcaça de frangos de corte submetidos a dietas com diferentes níveis de energia e aminoácidos - Laís Maria de Brito Lima Penha (2006)
The objective of this paper was to evaluate performance, carcass and parts yields and male and female broilers abdominal fat fed with different energy and amino-acids (aa) diet, respecting ideal protein concept. There were used Ross 308 broiler chick, male and female, fed with 3 diets formulated for starter (1-21 days), grower (22-40 days), and finisher (41-45 days). Experimental period was 1-45days. 3 Metabolized energy (ME) were used: low, medium and high: starter (2900; 3000 and 3100 Kcal/Kg), grower (3000; 3100 and 3200 Kcal/Kg) and finisher (3100; 3200 and 3300 Kcal/Kg), respectively. Two amino acids levels were used: normal (UFMG usage) and a higher with 10% over this. The design was completely randomized. Both sexes were analyzed separated. The differences among medias were analyzed with “SNK” test. The worst gain and consumption for 1-45days males was observed with low energy diets (P<0,05) and the amino acids levels made no influence. In females the gain weight was influenced by the higher energy and amino acids levels and was better when compared with others levels, but, without interactions. Without relationships with amino acids levels, males fed with higher energy levels shown worse carcass yields, and in females there were observed interaction. In males breast yield shown significative differences while increasing amino acids levels, without relationship with energy levels. For female there were interactions. Other parameters showed no significative differences.